Princesses in the Suburbs: Reading The Virgin Suicides as a Fairytale - Maharani, Moureta Lingkar; Mugijatna, ‎‎‎‎ (Jurnal Bahasa, Sastra, dan Studi Amerika, 2021)
The concept of male gaze has been present for a very long time. It is present in literature, albeit literature being an entirely different media. In The Virgin Suicides by Jeffrey Eugenides, this theme seems to be very apparent along with themes such as voyeurism and objectifications. Drawing on the structuralist and gender studies, this article emphasizes about the effect of the male gaze and how this specific way of viewing affects the girls in a way that it shifts their function as a character, by reading the novel as a fairytale—a form of literary work of which the elements are easy to understand—helped by Vladimir Propp’s theory of dramatis personae. The findings attained from literature reading and library research concludes that the way the neighborhood boys' view of the Lisbon girls does affect their roles in the story. I argue that the Lisbon girls were put on a very high pedestal since the very beginning; therefore positions them as the fairytale princess. However, due to the nature of the gaze applied in the work, there are possibilities that it may shift to other characters.